Dielectric and physicochemical characterization of Creole chicken breast meat for quality classification in the radiofrequency range - Wilson Castro; Jorge Chavez; Lusmenia Ruiz-Mejía; Thony Arce; Himer Avila-George; Tony Chuquizuta (PLoS ONE, 2026)
Understanding the quality attributes of poultry meat is essential for food safety, consumer satisfaction, and value chain efficiency. This study presents a proof-of-concept assessment of the physicochemical and dielectric properties of Creole chicken breast meat to classify samples into three quality categories: PSE (pale, soft, exudative), RFN (reddish, firm, non-exudative), and DFD (dark, firm, dry). A total of 96 samples were classified using pH at 24 h postmortem, yielding 3.13% PSE, 54.17% RFN, and 42.70% DFD. Dielectric spectroscopy in the 20 Hz to 1 MHz range revealed group-dependent spectral differences, most notably between 40 Hz and 2 kHz, where DFD meat showed higher ϵ ′ and ϵ ″ values under the evaluated conditions. The dielectric response was modeled using a two-dispersion approach, identifying α and β relaxation processes and differences in the α -relaxation frequency across categories (0.148 kHz for DFD, 0.105 kHz for RFN, and 0.127 kHz for PSE). Given the single-source sampling and the strong class imbalance, particularly the limited number of PSE samples, the findings should be interpreted as preliminary. Nevertheless, the results suggest that low-frequency dielectric parameters may be explored as candidates for rapid, non-destructive screening of meat quality categories, and they provide a reproducible workflow that can guide future validation studies and sensor-oriented designs in small-scale poultry production systems.